NLRP12-associated periodic syndrome: A description of the authors' own observation and an analysis of literature data - M. F. Dubko; E. N. Suspitsyn; A. P. Sokolenko; E. N. Imyanitov; T. S. Likhacheva; A. Yu. Kazantseva; O. V. Kalashnikova; V. G. Chasnyk; M. M. Kostik (Современная ревматология)
Autoinflammatory diseases (AIDs) are a group of rare disorders characterized by persistent or recurrent inflammation caused by the hyperactivation of mediators and innate immune cells (neutrophils, monocytes/macrophages). The paper describes the authors' own case of NLRP12-associated AIDs and the efficiency of canakinumab therapy and reviews a series of cases of the similar disease, which are given in the literature.